Translation Errors on Report Texts by the Fourth Semester Students at UIN Sayyid Ali Rahmatullah Tulungagung - Dessy Rahma Lestari; Nurul Chojimah (Universitas Pendidikan Mandalika, 2023)
This study aims to describe the phenomenon of errors in the English translation of semester IV students on report texts at UIN Sayyid Ali Rahmatullah Tulungagung (SATU). The research design is a descriptive design with a qualitative approach. The main data in this study is the results of the participants' translations of the report text and their interview answers. This study reveals four types of student errors in translating report texts into Indonesian: incomplete writing, mistranslation of pronouns, translation meaning errors, and sentence errors. Errors in giving meaning with inappropriate words are the most common mistakes made by students in this translation. While the factors that cause them to make mistakes in translation such as sloppy, lack of vocabulary, lack of vocabulary, and different structures between Indonesian and English.